ESL students communication apprehension and their choice of communicative activities - Wan Zumusni Wan Mustapha,; Noriah Ismail,; Deepak Singh Ratan Singh,; Suhaidi Elias @Alias, (Penerbit Universiti Kebangsaan Malaysia, 2010)
In order to examine the English communication apprehension (CA) of ESL students at the tertiary level, this study surveyed and analysed 50 students in their final year of the Bachelor in Business Administration (BBA) programme at UiTM Johor. The study looked at the types of English language activities preferred by the students, as well as those they perceived as helpful. The results indicate that the students have a comparatively high level of communication apprehension. The study also reveals that the students prefer group discussion as a way of reducing their communicative anxiety